"Wajah Kerahiman" Gereja di Hadapan Realitas Aborsi: Sebuah Pembacaan Teologis-Moral Kontekstual - Paskalis Lina (Jurnal Penelitian Pendidikan Agama Katolik, 2025)
The abortion issue still persists in Indonesia. In spite of the positive laws that regulate abortion, the fact remains that abortion is not easy to eliminate. Differences in religious perspectives have made moral judgment on abortion even more difficult. This article aims to present the view of the Catholic Church on abortion and also to propose solutions for the moral-pastoral formation of the perpetrators. Using a documentary method and interpreting from a perspective of Catholic moral theology, the author collects and reviews available data and documents in order to propose a contextual moral and pastoral approach to address abortion in Indonesia. The author found two important points, namely First, there are moral dilemmas in the act of abortion, both from the perspective of civil law and from the experience of the perpetrators. But these dilemmas cannot legitimize abortion. Second, a sound pastoral care toward forgiveness, hope and healing and moral guidance for those involved in abortion must be provided so that they do not fall back into the act of killing an innocent fetus.